IoT System Development and Implementation for ECG Signal Analysis and Visualization - Μπακόλας, Ιωάννης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Τεχνολογίας Πληροφορικής και Υπολογιστών, 2017)
The purpose of this diploma thesis is the design, development and implementation of an end-to-end ECG analysis and visualization IoT system using market ready technologies that can be used in real life medical applications and scenarios. For the development of the system we chose technologies and frameworks by taking account factors like cost, support, platform portability, backwards compatibility with older versions of software and hardware, power consumption, computational and networking load. The system consists of three main parts, the first part is the embedded Linux based application which reads the ECG signal and transmits it via classic or low energy Bluetooth to a smartphone or tablet. The second part is the android application that receives the ECG signal, stores it on the device, visualizes it (real-time visualization support on BLE connections) and sends it as a http packet through internet to the server for database storing. The last part is the webservice that runs on the server, its task is to receive the packet from the android app, evaluate that the packet has the right format and connect to the database to insert or update the record. The performance of every part of the system was validated by experimental evaluation of trade-offs that affect the run-time operation of all sub-systems, thus leading to the optimum configuration of the complete system.